Prevalence of Hypertension and diabetes mellitus in rural hilly regions of Uttarakhand state - Pandey, Arun; Bhatt, Sunil; Bhatnagar, Nitnav (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Introduction: Among the most common chronic non-communicable diseases worldwide, hypertension (HT) and Type 2 Diabetes mellitus (DM) are increasingly becoming a matter of public health importance. Limited studies on the prevalence of HT and DM have been performed in rural hilly regions of Uttarakhand state. Objectives: To estimate the prevalence of HT and DM and their association with some selected risk factors among adults in rural hilly areas of Uttarakhand. Methods: This cross-sectional study was carried out from August 2015 to October 2016 with a randomly selected sample of 401 adults in hilly region of Tehri Gharwal and Uttarkashi Districts of Uttarakhand. Demographic, anthropometric measures and lifestyle factors were obtained for all participants with the help of predesigned and pretested interview schedule. A subject with recorded systolic blood pressure of ≥ 140 mmHg or diastolic blood pressure of ≥ 90mmHg was considered hypertensive. Screening for DM was based on the following World Health Organization (WHO) criteria. Bivariate analysis was used to identify the association. Results: The mean age of the study population was 46.6 years ± 16.1 years. Mean BMI of the participants was 22.7 ± 4.8. It was found that 27.7 per cent of the subjects were current tobacco users while 24.7 per cent were current alcoholic. The overall prevalence of HT and DM were 31.4% and 4.7% respectively. About 2.5% of the study subjects were suffering from both HT and DM. The risk factors for HT in this study included age, BMI, vegetarian diet and increase salt intake. Age was found to be a significant risk factor for DM in the present study. Conclusions: A high prevalence of HT and DM in rural hilly areas of Uttarakhand need community outreach campaigns regularly for their early detection & proper health education. Jour of Diab and Endo Assoc of Nepal 2018; 2 (1): 29-30